ENHANCING RESEARCH CAPACITY OF PUBLIC HEALTH PERSONNEL THROUGH RESEARCH MANAGEMENT MODEL DEVELOPMENT: INTEGRATING AND ADAPTING THE TDR-TGHN COMPETENCY WHEEL - Khunpiluek, Issara; Sujimongkol, Chinakorn; Kaewsombat, Kuttiya (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
Public health research plays a crucial role in improving the quality of life and well-being of the population. However, enhancing the research capacity of public health personnel remains a significant challenge. This study focuses on developing a research management model to strengthen the research capacity of public health personnel by integrating and adapting the TDR-TGHN competency wheel framework. The study also aims to investigate the factors influencing the effectiveness of the adapted framework in developing research skills. Methods: This is an action research study employing a mixed-methods approach, including an experimental design, participatory observation, and analysis. The sample consists of 60 public health personnel working under the Loei provincial public health office, including physicians, dentists, pharmacists, professional nurses, and public health officials, between December 2023 and April 2024. Results: The findings reveal that the research management model adapted from the TDR-TGHN competency wheel framework is effective in developing the research skills of public health personnel at the provincial level. This effectiveness is assessed based on the level of knowledge, skills, and attitudes towards research among personnel after receiving training or participating in activities according to the improved model. Furthermore, an increase in the quantity and quality of research conducted by public health personnel is observed. Factors influencing the effectiveness of the adapted research management model include: 1) aligning the framework with the context and needs of public health personnel, 2) stakeholder participation, 3) availability of support resources, 4) a robust monitoring system, and 5) motivation and support from policy-level administrators. Discussion and conclusion: the evaluation should focus on measuring the practical impact of research derived from the new model, assessing whether it has led to changes in policies, practices, or the implementation of various measures, as well as improvements in health situations or indicators at the provincial level. Evaluation in different dimensions will provide in-depth information on the strengths, weaknesses, and areas for improvement of this newly adapted research management model, leading to the sustainable development of research capacity among public health personnel.